Pengaruh Pemberian Sarapan terhadap Konsenterasi Belajar pada Remaja - Putra, Muh Guntur Sunarjono; Kustiyah, Lilik; Dwiriani, Cesilia Meti; Septiani, Eka (Program Studi Gizi, Universitas Bumigora, 2025)
Breakfast was a meal at the start of the day that was often overlooked by teenagers, even though it played an important role in concentration and academic performance. This study aimed to analyze the eect of breakfast intervention on concentration in adolescents. The research method used a quasi-experimental study design with secondary data. Data processing was carried out from February to April 2025. The study subjects were divided into the intervention group (Cibungbulang Junior High School 1) and the control group (Cibungbulang Junior High School 2), with a purposive sampling technique. The inclusion criteria were that the subjects were in class VII, had no history of diabetes mellitus, and had complete data on the variables studied, while the exclusion criteriawere incomplete and irrational data.The statistical tests used were the Mann-Whitney dierence and Spearman correlation tests. The results showed signicant dierences in intake and levels of energy and nutrient adequacy between the intervention and control groups (p<0.05). The correlation test also showed a signicant relation- ship between intake and levels of energy and nutrient adequacy with adolescent learning concentration (p<0.05). Therefore, providing breakfast that met balanced nutritional guidelines was important to improve concentration and support adolescents' academic performance.